2020
DOI: 10.1038/s41598-020-76177-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicted climate change will increase the truffle cultivation potential in central Europe

Abstract: Climate change affects the distribution of many species, including Burgundy and Périgord truffles in central and southern Europe, respectively. The cultivation potential of these high-prized cash crops under future warming, however, remains highly uncertain. Here we perform a literature review to define the ecological requirements for the growth of both truffle species. This information is used to develop niche models, and to estimate their cultivation potential in the Czech Republic under current (2020) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Phenology studies require the involvement of scientists with different expertise from different countries. For example, the International Long Term Ecological Research network (ILTER) is a scientific network of over 600 research stations located in various ecosystems [280]. Similar research networks: "PhenoCam" (http://phenocam.sr.unh.edu/ webcam/, accessed on 17 December, 2021), "European Phenology Network (EPN)", and "Phenological Eyes Network (PEN)" (http://www.pheno-eye.org/, accessed on 17 December, 2021) were created for phenological observations in various types of vegetation: forests, meadows, or arable fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenology studies require the involvement of scientists with different expertise from different countries. For example, the International Long Term Ecological Research network (ILTER) is a scientific network of over 600 research stations located in various ecosystems [280]. Similar research networks: "PhenoCam" (http://phenocam.sr.unh.edu/ webcam/, accessed on 17 December, 2021), "European Phenology Network (EPN)", and "Phenological Eyes Network (PEN)" (http://www.pheno-eye.org/, accessed on 17 December, 2021) were created for phenological observations in various types of vegetation: forests, meadows, or arable fields.…”
Section: Discussionmentioning
confidence: 99%
“…The most common approach in review papers consists of bibliometric analyses of available journal databases [8,9,11,22,24,71,79,89,90,93,142,207,272,[277][278][279][280][281]. Publications included in the Web of Science Core Collection database were the basic material used in the present study; these were found using the following filters:…”
Section: Methodsmentioning
confidence: 99%
“…The main results obtained were (i) the supply chain will not change a lot in the next decade and the only expected variations would be the impact of some stakeholders and their weights, although one expert stated that changes could be expected at national but not at the international level; (ii) truffle producers will develop their own marketing network in order to sell directly on the retail markets or using online trading, although it seems not to be a homogeneous trend in all the Mediterranean area, expecting less changes in France; (iii) more online buying and selling of fresh and processed products is expected, as well as more consumption at country level and increase in truffles supply worldwide and yearround; (iv) with the increasing offer worldwide, there will be a price drop, if the market dimension remains the same, but it will be stabilized if the demand keeps the current global growing trend. In this context, local producers will seek to distinguish themselves through an environmentally friendly product or to develop territorial designations; (v) the decrease of wild production will continue due to forest and land management abandonment and climatic extreme events, such as long droughts, strong winds or heavy rain storms, although this trend will not be the same for all truffle species (climate change will differentially affect truffle species occurrence) [24]. With less consensus than the previous ones, we highlight: (vi) It is expected to have global competition, and thus truffles could lose their uniqueness (Table 1).…”
Section: Description Of the Supply Chainmentioning
confidence: 99%
“…France and Italy have produced an average of 43 and 19 tons per year, respectively, during the period 2013-2018 [14], however, there has not been the same increase during the last three seasons as in Spain. Australia, with 11 tons per year [24], and Chile, with 1.3 tons in 2020 [25], are also becoming players in the black truffle world arena.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in climate related to temperature and precipita-tion influence the changes of microbial communities because the climate changes lead to consequences for the changes of plant communities [43,44]. Ectomycorrhizal fungal species, which are host-dependent symbiotic fungi, are also closely related to changes in climate [44,45]. T. matsutake and truffle, which are ectomycorrhizal mushrooms with high ecological and economic values, are the most sensitive to changes in environmental conditions.…”
Section: Differences Between Microbial Communitiesmentioning
confidence: 99%